Interpersonal Subtypes and Therapy Response in Patients Treated for Posttraumatic Stress Disorder. (26th February 2015) - König, Julia; Onnen, Margarete; Karl, Regina; Rosner, Rita; Butollo, Willi
Abstract : Interpersonal traits may influence psychotherapy success. One way of conceptualizing such traits is the interpersonal circumplex model. In this study, we analyse interpersonal circumplex data, assessed with the Inventory of Interpersonal Problems (Horowitz, Strauß, & Kordy, 1994) from a randomized study with 138 patients suffering from posttraumatic stress disorder after trauma in adulthood. The study compared cognitive processing therapy and dialogical exposure therapy, a Gestalt‐based intervention. We divided the interpersonally heterogeneous sample according to the quadrants of the interpersonal circumplex. The division into quadrants yielded subgroups that did not differ in their general psychological distress, but the cold‐submissive quadrant tended to exhibit higher posttraumatic stress disorder symptom severity and interpersonal distress than the other three. There was also a trend for patients in different quadrants to be affected differently by the treatments. Correlation analyses supported these results: in cognitive processing therapy, more dominant patients had more successful therapies, while in dialogical exposure therapy, success was not correlated with interpersonal style. Results indicate that especially patients with cold interpersonal styles profited differentially from the two treatments offered. Dividing samples according to the interpersonal circumplex quadrants seems promising. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner Message: Interpersonal traits may contribute to psychotherapy outcome. Dividing the sample according to the quadrants of the interpersonal circumplex, as opposed to cluster analysis, yielded promising results. Patients higher in dominance fared better with cognitive processing therapy, while interpersonal style had no correlations with therapy success in dialogical exposure therapy.